2016
DOI: 10.1051/matecconf/20179001027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rear-roof spoiler on the aerodynamic performance of hatchback vehicle

Abstract: Abstract. Rear-roof spoiler is commonly used for improving the aerodynamic performance of road vehicles. This study aims to investigate the effect of strip-type rear-roof spoiler on the aerodynamic performance of hatchback vehicles. The main parameter of study was the inclination angle of the spoiler. A computational fluid dynamics (CFD) method was used. The numerically obtained results were compared to the experimental data for validation of the CFD method. The spoiler effectively reduced the aerodynamic lift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This is caused mainly for that reason that equivalent val-ues of driving resistance (aerodynamic resistance, acceleration resistance, etc.) can be assigned for each vehicle condition [4]. Fig.…”
Section: Analysis Of the Selected Vehicle Performance Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…This is caused mainly for that reason that equivalent val-ues of driving resistance (aerodynamic resistance, acceleration resistance, etc.) can be assigned for each vehicle condition [4]. Fig.…”
Section: Analysis Of the Selected Vehicle Performance Parametersmentioning
confidence: 99%
“…This performance is applicable to overcome the driving resistance (it includes especially aerodynamic resistance, acceleration resistance, etc.) [4,6].…”
Section: Maximum Performance At the Wheels Depending On The Vehicle Smentioning
confidence: 99%
See 1 more Smart Citation
“…A numerical study performed by Cheng and Mansor [9] with the Ahmed model [10] included a simple rear spoiler that helped to identify the expected trends of making this type of modification. It was found that downforce increases as the spoiler angle rises due to flow deceleration upstream of this device.…”
Section: Rear Spoilersmentioning
confidence: 99%